QUANTUM COMPUTING: TERMINOLOGY, APPLICATIONS, SECURITY AND BEYOND - Karimov , Madjit Malikovich; Tashev, Komil; Safoev , Nuriddin (Innovative Development in Educational Activities, 2023)
Quantum computing diverges from classical computing by leveraging principles rooted in quantum mechanics, making use of distinctive features such as entanglement and superposition. The pivotal distinction between a quantum computer and its classical counterpart lies in its remarkable capacity to process information at an exceptionally accelerated rate, a capability facilitated by the concept of quantum entanglement. Interest in the phenomenon of quantum entanglement has experienced exponential growth in recent years, with the past decade witnessing notable advancements in the practical implementation of quantum computation within the realm of quantum information. This investigation systematically curated secondary resources from various databases spanning nearly a century, employing specific keywords. The ensuing presentation encapsulates the fundamentals of quantum computing, its applications, and the pivotal role played by quantum entanglement. Consequently, this research contributes to a comprehensive understanding of quantum computing, its applications, and the significance of quantum entanglement in the field.